2012
DOI: 10.31436/iiumlj.v18i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Wife’s Rights to Maintenance: Husband’s Duty to Maintain a Working Wife in Islamic Law and the Law in Malaysia

Abstract: Islamic law imposes a duty on the husband to maintain his wife. This duty arises as soon as the marriage contract is completed. The duty to maintain her continues until the contract of marriage ends either through death or separation. This paper seeks to examine the provisions of Islamic law on the husband’s duty to maintain a working wife. The examination extends to the adequacy of provisions of the law in Malaysia governing maintenance of a Muslim wife. The paper will further analyze the law on the extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The different schools of though in Islam have defined "nafaqah" to basically refer to the basic needs. However, the Shafi'i jurists have expanded the meaning to include food, clothing, cleaning tools, house appliances like cooking equipment, accommodation and servant in the case where the wife ever used the service of a servant before her marriage [27].…”
Section: What Is the Position On Wife Maintenance Under Islamic Law A...mentioning
confidence: 99%
See 4 more Smart Citations
“…The different schools of though in Islam have defined "nafaqah" to basically refer to the basic needs. However, the Shafi'i jurists have expanded the meaning to include food, clothing, cleaning tools, house appliances like cooking equipment, accommodation and servant in the case where the wife ever used the service of a servant before her marriage [27].…”
Section: What Is the Position On Wife Maintenance Under Islamic Law A...mentioning
confidence: 99%
“…[30] 2) She must be a major person and therefore to have sexual relationship. [31] 3) The marriage must be a valid marriage. [31] 4) The wife's right to maintenance must be unaffected by certain factors which disentitle her to maintenance, for example, disobedience (nusyuz) [31] From the conditions set out above, it could be observed that a wife loses her right to maintenance when she is disobedient or nusyuz.…”
Section: What Is the Position On Wife Maintenance Under Islamic Law A...mentioning
confidence: 99%
See 3 more Smart Citations